The Effect of Brand Image and Electronic Word of Mouth on Xiaomi Smartphone Purchasing Decisions - Huwae, Victor Ernest; Tabelessy, Walter; Tamher, Etvin Rizal; Tehuayo, Erlinda; Lewaherilla, Novalien Carolina (UIN Sunan Gunung Djati, 2023)
Brand image and electronic word of mouth still have limitations, so an analysis of brand trust was carried out to mediate the influence of brand image and E-WoM on purchasing decisions. Brand trust can mediate the relationship between brand image and E-WoM on purchasing decisions. This research aimed to determine the influence of brand image and electronic word of mouth on purchasing decisions through brand trust as a mediating variable. This type of research is quantitative research. This research's data type is quantitative, and the data source used primary data. The population in this study were all Pattimura University students and the number of samples was 104. The sampling method used was non-probability sampling using the purposive sampling technique. The data analysis method uses Partial Least Square (PLS), and the data was processed using SmartPLS software version 3.3.3. This research shows that Brand Image influences Purchasing Decisions through Brand Trust with a path coefficient value of 0.185, T-statistics of 3.178 and P-values of 0.002. It means that the Brand Image variable has an indirect positive and significant influence on the Purchase Decision variable through the Brand Trust variable because it has path coefficient values in the range of 0 to 1 and has T-statistic values > 1.96 and P-values < 0.05. Electronic word of mouth influences purchasing decisions through brand trust with a path coefficient value of 0.240, T-statistics of 2.368 and P-values of 0.018. It means that the electronic word-of-mouth variable has a positive and significant indirect influence on the Purchasing Decision variable through the Brand Trust variable because it has a path coefficient value in the range of 0 to 1 and a T-statistic value > 1.96 and also P-values < 0, 05.